IMPLEMENTASI WEB CAMERA SEBAGAI VISUAL INSPECTION OTOMATIS UNTUK PROSES PEMUTUAN UKURAN DAN TINGKAT KEMATANGAN BUAH TOMAT - Andrizal andrizal; Dodon Yendri; Aulia Rossalina (Teknik Elektro Politeknik Negeri Padang, 2012)
Quality and sorting is one method to classify an observed object and the end result of the inspection process. Quality and sorting can be done manually or automatically where quality and one manually sorting can be done by utilizing the human senses. Quality automatically requires certain tools such as the use of digital cameras to replace the sensory function of the human eye as a visual inspection. By using a digital camera, the camera capture object images obtained is processed via image processing, the processing system can be used as an automated visual inspection for the decision making process quality and sorting. The ability to recognize objects in the form of camera pixel component, can be used to determine the size and color, while the components can be used to determine the level of maturity. This system implemented as automatic visual inspection to determine quality tomato fruit size and maturity level. Results of testing this system is able to recognize 100% ripe tomatoes and 73% were able to recognize the young tomato fruit, the overall ability of the system to recognize the maturity level of the tomato fruit was 86.15%. While the tomatoes quality test based on class size with large, medium and small work 100%. Recognize the success rate of fruit maturity is greatly influenced by the current lighting objects tomatoes in camera capture. We hope this research can be used as input data for the next stage as the data input to the system pemutuan and automatically sorting tomatoes.